Addressing gaps in our understanding of the drowning patient: a protocol for the retrospective development of an Utstein style database and multicentre collaboration. Issue 2 (9th February 2023) - Thom, Ogilvie; Roberts, Kym; Leggat, Peter A; Devine, Susan; Peden, Amy E; Franklin, Richard Charles
Abstract : Introduction: This retrospective observational study aims to create a comprehensive database of the circumstances of drowning (including care provided and outcomes of care) to report against the Utstein style for drowning (USFD) for patients presenting to the emergency department (ED). Four areas will be examined: a feasibility study of the USFD; a comparison of classification and prognostication systems; examination of indications and efficacy of different ventilation strategies; and differences in the circumstances, severity, treatment and outcomes of drowning by sex and gender. Methods and analysis: This protocol outlines retrospective data collection for all patients presenting to EDs of the Sunshine Coast Hospital and Health Service in Queensland, Australia with the presenting problem or discharge diagnosis of drowning or immersion between 2015 and 2022. Patients computerised health records (emergency medical service record, pathology, radiology results, medical and nursing notes for ED, inpatient units and intensive care units) will be used to extract data for entry into an USFD database. Descriptive (eg, median, IQR) and inferential statistical analyses (eg, analysis of variance) will be used to answer the separate research questions. Development of an International Drowning Registry using the USFD dataset and the Research Electronic Data Capture (REDCap) web application is discussed. Ethics and dissemination: This study has been approved by Metro North Human Research and Ethics Committee (Project No: 49754) and James Cook University Human Research Ethics Committee (H8014). It has been endorsed by national drowning prevention organisations Royal Life Saving Society Australia (RLSSA) and Surf Life Saving Australia (SLSA). Study findings will provide data to better inform clinical management of drowning patients and provide an evidence base on sex and gender differences in drowning. Results will be disseminated through peer review publications, conference presentations and media releases. Results will also be disseminated through RLSSA and SLSA membership of the Australian and New Zealand Resuscitation Council and the Australian Water Safety Council.